Representações sobre a inclusão de crianças com transtorno do espectro autista em Vacaria/RS: contribuições da história cultural e do ensino de história para o combate à estigmatização - Silva, Catiana Viero da (My University, 2026)
This dissertation, linked to the Professional Master's Program in History, within the research line Languages and Culture in History Teaching, investigates the representations of the school inclusion of children with Autism Spectrum Disorder (ASD) in early childhood education in the municipality of Vacaria/RS, from an intersectional approach grounded in Cultural History. Anchored in the contributions of Sandra Pesavento (2003; 2008), the research understands representations as symbolic constructions, socially and historically produced, that guide practices and discourses in the educational context. From this perspective, the teaching of History is conceived as a strategic field for problematizing the social narratives that constitute the imaginary about disability and autism, contributing to the deconstruction of exclusionary conceptions and to the production of an inclusive school culture. Of a qualitative nature, the study adopted oral history and Discursive Textual Analysis as methodological procedures, according to Roque Moraes and Maria do Carmo Galiazzi (2007). Data production was carried out through semi-structured interviews conducted with early childhood education teachers, a pioneering teacher in the inclusion process in the municipality, a psychologist from the municipal network, and the mother of a child with ASD, whose school trajectory constitutes the guiding thread of the analysis. The interpretation of the data was guided by an intersectional perspective, considering social markers such as gender, race, social class, teacher training, and working conditions. The results show that the school inclusion of children with ASD is configured as a historical, social, and pedagogical process in permanent construction, marked by advances and tensions, in which early childhood education assumes a central role in welcoming, sensitive observation, and early identification of signs of the disorder. It is concluded that inclusion goes beyond compliance with legal regulations, constituting an ethical and political commitment that requires the construction of pedagogical practices based on the recognition of diversity and co-responsibility between school, family, and public policies. [resumo fornecido pelo autor]
A presente dissertação, vinculada ao Programa de Pós-Graduação em História Mestrado Profissional, na linha de pesquisa Linguagens e Cultura no Ensino de História, investiga as representações sobre a inclusão escolar de crianças com Transtorno do Espectro Autista (TEA) na educação infantil no município de Vacaria/RS, a partir de uma abordagem interseccional e fundamentada na História Cultural. Ancorada nas contribuições de Sandra Pesavento (2003; 2008), a pesquisa compreende as representações como construções simbólicas, social e historicamente produzidas, que orientam práticas e discursos no contexto educacional. Nessa perspectiva, o ensino de História é concebido como um campo estratégico para a problematização das narrativas sociais que constituem o imaginário sobre a deficiência e o autismo, contribuindo para a desconstrução de concepções excludentes e para a produção de uma cultura escolar inclusiva. De natureza qualitativa, o estudo adotou como procedimentos metodológicos a história oral e a Análise Textual Discursiva, conforme Roque Moraes e Maria do Carmo Galiazzi (2007). A produção dos dados ocorreu por meio de entrevistas semiestruturadas realizadas com professoras da educação infantil, uma professora pioneira no processo de inclusão no município, uma psicóloga da rede municipal e a mãe de uma criança com TEA, cuja trajetória escolar constitui o fio condutor da análise. A interpretação dos dados foi orientada por um olhar interseccional, considerando marcadores sociais como gênero, raça, classe social, formação docente e condições de trabalho. Os resultados evidenciam que a inclusão escolar de crianças com TEA configura-se como um processo histórico, social e pedagógico em permanente construção, marcado por avanços e tensões, no qual a educação infantil assume papel central no acolhimento, na observação sensível e na identificação precoce de sinais do transtorno. Conclui-se que a inclusão ultrapassa o cumprimento de normativas legais, constituindo-se como um compromisso ético e político que exige a construção de práticas pedagógicas pautadas no reconhecimento da diversidade e na corresponsabilização entre escola, família e políticas públicas. [resumo fornecido pelo autor]
Keywords: História - Estudo e ensino; Transtornos do espectro autista; Inclusão escolar - Vacaria (RS); History - Study and teaching; Autism spectrum disorders; Mainstreaming in education - Vacaria (Brazil)